Pengaruh Likuiditas, Leverage, Ukuran Perusahaan, Dan Kepemilikan Manajerial Terhadap Manajemen Laba Dengan Financial Distress Sebagai Variabel Mediasi : (Survei Pada Perusahaan Pertambangan Yang Terdaftar Di Bursa Efek Indonesia Tahun 2019-2023) - Oneng, Muthia Yogelina; Muliati, Muliati; Pakawaru, Muhammad Ilham; Tanra, Andi Ainil Mufidah (Politeknik Negeri Ambon, 2025)
Introduction: This study employs financial hardship as a mediating variable to examine the impact of managerial ownership, firm size, liquidity, and leverage on earnings management. Companies in the mining industry that were listed on the Indonesia Stock Exchange (IDX) between 2019 and 2023 are the subjects of this study. Methods: This study takes a quantitative approach, processing data with WarpPLS 8.0 software and employing multiple linear regression analysis and route analysis approaches. Secondary data from documentation studies of the Indonesia Stock Exchange, the company's annual financial reports, and other official sources were used. Results: A purposive selection approach was used to choose 19 mining businesses as samples that satisfied the study's requirements, yielding a total of 95 observations from the study's population of 63 mining companies. The findings indicated that while managerial ownership had a large negative impact on earnings management, leverage had a considerable beneficial impact. Earnings management was not significantly impacted by liquidity, firm size, or financial crisis. The association between leverage and earnings management was only significantly mediated by financial hardship in the mediation test; other mediations did not show any meaningful effects. Keywords: Likuiditas, Leverage, Manajemen Laba, Financial Distress